A REVIEW ON PHYTOSOMES: NOVEL APPROACH FOR HERBAL PHYTOCHEMICALS - Kumar, Arun; Kumar, Bimlesh; Singh, Sachin Kumar; Kaur, Barinder; Singh, Saurabh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â The poor oral bioavailability of polyphenolic compound can be enhanced through the incorporation of them into phospholipid based self-assembled delivery system, i.e. popularly known as phytosome. Phytoâ€ means plants and someâ€ resembles a covering around/or a structure. Phytosome is generally prepared by reacting one or two moles of polyphenolic phytoconstituents and phospholipid. It may be either in the ratio of 1:1 and 1:2. By using phytosomes, one can also achieve enhanced rate and extent of the passage of lipophilic herbal constituents across lipid membrane that explains its character as a carrier as well as acid labile herbal drugs could also be protected in gastrointestinal tract. There are number of products available in the market that contains phytosomal drug delivery system such as Ginkgo biloba, Silybum marianum, and Camellia sinensis. The present review describes an updated overview of preparation of phytosomes, advancement in phytosomes technology, various herbal drugs for which phytosomes have been used as a carrier, its commercial availability and applications.